Chemical characterization of some soils from four counties that produce flue-cured tobacco (2012)
The municipalities or counties of Campoalegre and Garzon (State of Huila) and Capitanejo and Enciso (State of Santander) show different chemical soil characteristics when their origin is taken into account, based on their edaphogenetic environments. For the characterization of the soils from these counties, samples from 65 farms were arranged, based on the database of farmers associated with the Protabaco Company. With the soil samples taken, chemical and texture analyses were performed, codifying the results in order to analyze them, keeping in mind the ideal parameters for the tobacco crop. In the counties of Huila, the texture, pH and organic matter were found to have ideal levels, in contrast to the phosphorus, potassium, magnesium, sulfur and chloride levels which were unsuitable, but the calcium content showed levels between suitable and good. In Santander, the pH, organic matter, phosphorus, calcium, sulfur and chloride were at unsuitable levels, in contrast, the contrary occurred with the texture and potassium which were at normal levels. It is recommended, due to the difference among the chemical parameters, that a fertilization program be handled differently for the zones of Santander and Huila, bearing in mind that the chemical parameters were found to be more limited in Santander than in Huila.